FERMENTASI BLOTONG LIMBAH PG. KREBET DAN RUMEN SAPI DALAM PRODUKSI BIOGAS - Pramono Sasongko; Lorine Tantalu (BUANA SAINS, 2018)
Sugar Cane Filter Cake (SGFC) is the sugar cane to sugar processing waste in Krebet Baru Sugar Factory. Utilization of this SGFC waste was limited for free soil or unprocessed fertilizer. Sugar cane filter cake is an organic waste which potential to be utilized into biogas. Biogas is anaerobic process product which consist methane as a major compound. Factors that influence biogas fermentation process were temperature, water content, fiber, total sugar and total concentration of methanogen bacteria inoculum. Natural source of methanogenic bacteria is in the contents of the cattle rumen. The aim of this study was to determine the characteristics of blotong and the effect of addition of cattle rumen on biogas fermentation from the SGFC of the Krebet Sugar Factory. The first stage of this research was Blotong characterization. The second stage was spontaneous fermentation with two treatment factors. The first factor was enhancing the contents of the cattle rumen (5%) and without the addition of cattle rumen (0%). The second factor is the fermentation time with 3 different levels (20, 25 and 30 days). The results were shown that blotong had water content, fiber content, and C / N ratio were 10.71%; 0.06%; and 17: , respectively. These results indicate the potential of the blotong as a raw material for biogas production. SGFC fermentation with the addition of 5% cattle rumen content was shown the best results compared to biogas production with pure SGFC. The highest volume and yield of biogas produced were obtained from the 30-day fermentation process with the results of 37,327 ml of gas and 746.5 x 10-6 m3/kg. All flame tests show positive results and are proven to produce blue flames.